Assessing measurement gap using modern test theory: An investigation in Malaysian business organizations - Jusoh, Muhammad Shahar; Yusoff, Rushami Zien; Abas, Zakaria; Din, Mohd Salleh (PalArch's Journals, 2020)
Instrument construct is one of the most important issues in conducting research. Without proper consideration in tackling the issue, it is difficult for the instrument to be considered as valid and reliable. If construct validity is accurate, then it will provide a clearer and more precise descriptive analysis on the concepts being investigated. The most important criteria that need to be considered in answering the construct validity are reliability and validity. In traditional measurement model, the understanding of reliability and validity is totally different from the one offer by Rasch model from the context of ordinal data and interval data related issues. Regardless of the difference, this study is giving and sharing the other options of measuring an instrument in business and management natures for measuring the proposed framework. Using this model, local dependence and item fit are most considered in getting valid, reliable, and consistent, hence its significance to measure the construct. Finally the study applies goodness of measure purposely to answer issues related to validity and reliability tests. Principal components analysis was carried out to test the construct of questionnaires used in the study.